Planning a sanitary wastewater drainage system for Drivenik settlement (Proceedings of Faculty of Civil Engineering, 2025)
The settlement of Drivenik is located in the hinterland of the City of Crikvenica, within the administrative boundaries of the Vinodol Municipality. Currently, there is no systematic solution for sanitary wastewater drainage system in this area; instead, wastewater is managed individually through septic tanks, which is not sustainable in the long term from the perspective of environmental protection and public health. As part of this study, a conceptual design for a sanitary wastewater drainage system for the settlement of Drivenik has been proposed. The objective of the proposed solution is to meet the technical requirements related to the construction of connections, as well as overcoming of terrain obstacles along the planned collectors route, while simultaneously optimizing the length of the sewer collectors, reducing pipe diameters, and minimizing the need for construction of additional installations. In accordance with the Spatial Plan of the Vinodol Municipality proposal, the sanitary wastewater from Drivenik is intended to be conveyed to the central wastewater treatment plant serving the City of Crikvenica. Implementation of the proposed sewage system would enable efficient and environmentally acceptable collection, transport, treatment, and discharge of wastewater, while maintaining costeffectiveness in terms of construction and maintenance. As part of the study, a layout scheme of the sanitary wastewater drainage system for the settlement of Drivenik, all relevant hydraulic and structural calculations for the collectors, as well as calculations for the pumping stations were developed. Additionally, a corresponding approximate bill of quantities for the planned works required for the implementation of the system was prepared.
Keywords: wastewater sewage systems; orizontal management of the sewer network; sanitary wastewater; conceptual design; hydraulic design; structural calculations of pipes; pump stations; settlement of Drivenik